2000
DOI: 10.1038/sj.cgt.7700111
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Ku86 RNA antisense decreases the radioresistance of human fibroblasts

Abstract: Ku86 has been shown to be involved in DNA double-strand break (DSB) repair and radiosensitivity in rodents, but its role in human cells is still under investigation. The purpose of this study was to evaluate the radiosensitivity and DSB repair after transfection of a Ku86-antisense in a human fibroblast cell line. Simian virus 40-transformed MRC5V1 human fibroblasts were transfected with a vector (pcDNA3) containing a Ku86-antisense cDNA. The main endpoints were Ku86 protein level, Ku DNA end-binding and DNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
3
22
0
2
Order By: Relevance
“…4 and 5). These experiments are consistent with the demonstration that the expression of Ku86 antisense RNA in human cells leads to cellular defects in DNA DSB repair and cell proliferation (50,51). Thus, our data suggest that species differences exist in the requirement for Ku86 and that Ku86 performs an essential function in human cells.…”
Section: Discussionsupporting
confidence: 91%
“…4 and 5). These experiments are consistent with the demonstration that the expression of Ku86 antisense RNA in human cells leads to cellular defects in DNA DSB repair and cell proliferation (50,51). Thus, our data suggest that species differences exist in the requirement for Ku86 and that Ku86 performs an essential function in human cells.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicated that Ku is the major DNA end binding activity in cell extracts (30). As shown in Fig.…”
Section: Ku Represses the Transcription Controlled By The Hiv-1 Ltr Imentioning
confidence: 77%
“…Thus, to address that issue in human cells, chronically HIV-1-infected U1 cells bearing integrated proviruses were transduced with a retroviral vector carrying a Ku80 full-length antisense RNA. Indeed, the antisense strategy can be used to study the effect of Ku depletion in human cells, as it was demonstrated that antisense sequences directed against Ku80 were capable of impairing the expression of the protein in human cell lines, notably human colon carcinoma cells HCT116 (31) and human fibroblast cells MRC5V1 (30). Antisense directed against Ku70 were also used to deplete human T cell lymphoma MT2 cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Antisense and siRNA strategies Marangoni et al (2000b) used a full-length inverted cDNA to target Ku80 in human fibroblast cell lines. This resulted in a DRF at 10% IR survival of B1.7 for stable cell lines expressing the Ku80 antisense compared to control cell lines, which was likely a consequence of reduced DNA end-binding capacity and DSB repair rates observed in these cells.…”
Section: Molecular Targeting Of Dna-pkmentioning
confidence: 99%